2004
DOI: 10.1038/nm982
|View full text |Cite
|
Sign up to set email alerts
|

The membrane-cytoskeleton linker ezrin is necessary for osteosarcoma metastasis

Abstract: Metastatic cancers, once established, are the primary cause of mortality associated with cancer. Previously, we used a genomic approach to identify metastasis-associated genes in cancer. From this genomic data, we selected ezrin for further study based on its role in physically and functionally connecting the actin cytoskeleton to the cell membrane. In a mouse model of osteosarcoma, a highly metastatic pediatric cancer, we found ezrin to be necessary for metastasis. By imaging metastatic cells in the lungs of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

29
613
3
9

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 638 publications
(655 citation statements)
references
References 23 publications
29
613
3
9
Order By: Relevance
“…Therefore, considering the nature of this multi‐institutional study, we felt it necessary to omit the data for ALP and LDH. However, it is likely that the inclusion of these serological markers or known molecular markers such as P‐glycoprotein,31 CXCR4,32 and ezrin33 would improve the predictive ability of future nomograms. Fifth, the trunk cases had better outcomes than expected (better than proximal humerus cases) with respect to MFS.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, considering the nature of this multi‐institutional study, we felt it necessary to omit the data for ALP and LDH. However, it is likely that the inclusion of these serological markers or known molecular markers such as P‐glycoprotein,31 CXCR4,32 and ezrin33 would improve the predictive ability of future nomograms. Fifth, the trunk cases had better outcomes than expected (better than proximal humerus cases) with respect to MFS.…”
Section: Discussionmentioning
confidence: 99%
“…20 In a mouse model of osteosarcoma, ezrin was necessary for metastasis, and in dog tumors, a high expression of ezrin was associated with the early development of metastasis. 8 A relationship was also shown between high expressions of ezrin and poor outcome in 19 pediatric osteosarcoma patients. 8 More importantly, using dominant-negative mutants, antisense RNA or RNA interference, both groups demonstrated that ezrin overexpression is not only sufficient for metastatic progression, but it is also necessary, at least in these experimental systems.…”
mentioning
confidence: 89%
“…6,7 The identification of ezrin expression is a necessary component in osteosarcoma metastasis and it makes the study of this protein crucial in understanding the molecular pathways involved in metastatic diffusion. 8 Ezrin, the product of the Vil2 gene, is present in the cytoplasm in an inactive form but after threonine and tyrosine phosphorylation, ezrin assumes an active form, moving to the cell membrane and tethering F-actin to the cell membrane. 9 Ezrin has been associated with the formation of specialized cell surface domains and assists in the placement of molecules within these structures.…”
mentioning
confidence: 99%
“…CD44 and ezrin play important roles in promoting tumor metastasis (Yu et al, 1997;Stamenkovic 1999, 2000;Yu et al, 2004;Khanna et al, 2001Khanna et al, , 2004, whereas merlin acts as a tumor suppressor (Rouleau et al, 1993;Trofatter et al, 1993;Lutchman and Rouleau, 1995;Sherman et al, 1997;McClatchey et al, 1998;Giovannini et al, 1999Giovannini et al, , 2000. Thus far, the functional relationship between CD44 and merlin and the manner in which CD44 affects the tumor-suppressing activity of merlin have not been established.…”
Section: Increased Expression Of Merlin Inhibits the Binding Of Fluormentioning
confidence: 99%